PERKEMBANGAN KETERAMPILAN PENGUKURAN SISWA SD MELALUI PERMAINAN PENTENG - Mufarrahatus Syarifah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
This study was conducted through three phases, namely experimental preparation, design trials, and activity analysis. The learning design designed in this study aims to develop students' skills in measuring. The design involves traditional game namely penteng. Subject of this study is third grade students. The result of this study shows that students’ skill in measuring develop through their activities in using nonstandard measurement tool when they are playing penteng. When playing penteng, students measure the distance of the short wood fall to the hole where the wooden throw using long wood and short wood. The experience they get directly when taking measurements using short wood and jangers delivers them in stating distance using standard units. This is indicated by the process of counting jumps by students when asked to declare the results of non-standard calculation into the standard unit. Through these activities students' skills in measurement can develop